Legal Perspective On Holiday Benefits For Workers During Pandemic - Muhammad Zulfikar Al Ayyubi Firdaus; Muhammad Selfano Nur Hidayat; Irwan Setya Pambudi; Riki Setia Budi; Mawardha Indrasvari; Kent Adytia Kusnanto (Universitas Muhammadiyah Surakarta, 2022)
Indonesia is a country of law based on Pancasila and law. In Indonesia, labor issues are regulated in the law in Law No. 13 of 2003, as well as Government Regulation No. 78 of 2015 concerning wages and Regulation of the Minister of Manpower of the Republic of Indonesia Number 6 of 2016 concerning holiday allowances. Holiday allowances are wages for workers that are not basic wages. Holiday allowances are a right for workers. However, regarding violations of companies that do not pay for holidays, there are no criminal sanctions that are less clear. In this study, researchers used study literature which is used in collecting data from relevant journals or sources. In this study will examine the legal perspective on holiday allowances for workers in accordance with the Regulation of the Minister of Manpower Number 6 of 2016.